2004
DOI: 10.1074/jbc.m312649200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Carboxyl Terminus in ClC Chloride Channel Function

Abstract: The human muscle chloride channel ClC-1 has a 398-amino acid carboxyl-terminal domain that resides in the cytoplasm and contains two CBS (cystathionine-␤-synthase) domains. To examine the role of this region, we studied various carboxyl-terminal truncations by heterologous expression in mammalian cells, whole-cell patch clamp recording, and confocal imaging. Channel constructs lacking parts of the distal CBS domain, CBS2, did not produce functional channels, whereas deletion of CBS1 was tolerated. ClC channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 31 publications
(46 reference statements)
6
78
4
Order By: Relevance
“…Moreover, they observed that mutations in the COOH terminus did not alter the gating properties of the channel but cause a decrease in the maximal current. Surprisingly, Hebeisen et al (18) found that the deletion of CBS1 but not that of CBS2 was tolerated, in complete contrast to the results of Estévez et al (12) (FIGURE 4). These two studies underline the difficulties involved in investigating the role of CBS domains.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Moreover, they observed that mutations in the COOH terminus did not alter the gating properties of the channel but cause a decrease in the maximal current. Surprisingly, Hebeisen et al (18) found that the deletion of CBS1 but not that of CBS2 was tolerated, in complete contrast to the results of Estévez et al (12) (FIGURE 4). These two studies underline the difficulties involved in investigating the role of CBS domains.…”
Section: Discussioncontrasting
confidence: 49%
“…The conclusion of Hebeisen et al was mainly based on the use of concatameric constructs in which one of the subunits bore a point mutation (S537F) that renders the channel less sensitive to block by 9-AC (13). The authors assumed that 9-AC block represents a property of a single pore not influenced by the neighboring subunit (18). However, this assumption is probably not true, because results with ClC-0 indicate a dependence of 9-AC and CPA…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Although the physiological role of CBS domains is still unknown, truncations removing parts of the distal CBS domain of ClC channels abolished functional expression in heterologous systems (20,36).…”
Section: Discussionmentioning
confidence: 99%